PENGARUH LATIHAN KEKUATAN OTOT LENGAN TERHADAP HASIL PUKULAN SERVIS ATAS FLOATING BOLA VOLI PADA PESERTA EKSTRAKURIKULER BOLA VOLI SMK AL-IHYA SELAJAMBE KABUPATEN KUNINGAN - Iman Firmansyah; Dedi Iskandar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effect of arm muscle strength training on the performance of overhead floating serve in volleyball among extracurricular participants at SMK Al-Ihya Selajambe, Kuningan Regency. The background of this research is the difficulty faced by many students in mastering the basic technique of the overhead floating serve correctly, thus requiring specific training to improve this skill. The research method used was an experimental approach with a one- group pretest-posttest design. The sample consisted of 10 students selected using purposive sampling. The research instrument was a floating serve skill test conducted before (pretest) and after (posttest) the treatment, which consisted of push-up training for 10 sessions over 5 weeks.The results showed an increase in the average score from 18.10 in the pretest to 24.40 in the posttest. The normality and homogeneity tests indicated that the data were normally distributed and homogeneous. The hypothesis test using a paired samples t-test obtained a significance value of 0.000 (p < 0.05), indicating a significant effect of arm muscle strength training on the overhead floating serve performance. Therefore, it can be concluded that arm muscle strength training is effective in improving the overhead floating serve performance in volleyball extracurricular participants at SMK Al-Ihya Selajambe, Kuningan Regency.